2021
DOI: 10.1017/s0031182021000184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological description of the first Hepatozoon (Apicomplexa: Hepatozoidae) species infecting a neotropical turtle, with an approach to its phylogenetic relationships

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…It has proven useful for molecular screening of Hepatozoon and species descriptions in snakes (O'Dwyer et al ., 2013; Borges-Nojosa et al ., 2017; Ùngari et al ., 2018, 2021), including in our study. Yet, in recent years the need for the improvement and employment of other genetic markers capable of responding more clearly to the phylogenetic relationships of the group has been discussed (Abdel-Baki et al ., 2014; Maia et al ., 2016; Cook et al ., 2018; Gutiérrez-Liberato et al ., 2021; Hrazdilová et al ., 2021). In the recent differentiation of Hepatozoon catesbianae (Stebbins, 1903), Hepatozoon clamatae (Stebbins, 1905) and a third Hepatozoon genotype infecting frogs, the 18S rRNA marker identified low molecular divergence, and was found to be inadequate for the differentiation of these species (Léveillé et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has proven useful for molecular screening of Hepatozoon and species descriptions in snakes (O'Dwyer et al ., 2013; Borges-Nojosa et al ., 2017; Ùngari et al ., 2018, 2021), including in our study. Yet, in recent years the need for the improvement and employment of other genetic markers capable of responding more clearly to the phylogenetic relationships of the group has been discussed (Abdel-Baki et al ., 2014; Maia et al ., 2016; Cook et al ., 2018; Gutiérrez-Liberato et al ., 2021; Hrazdilová et al ., 2021). In the recent differentiation of Hepatozoon catesbianae (Stebbins, 1903), Hepatozoon clamatae (Stebbins, 1905) and a third Hepatozoon genotype infecting frogs, the 18S rRNA marker identified low molecular divergence, and was found to be inadequate for the differentiation of these species (Léveillé et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(2021), but diverged from the positioning of some lineages in the study by Guitiérrez-Liberato et al . (2021). In this case, our phylogenetic tree reveals that Hepatozoon simidi Guitiérrez-Liberato et al ., 2021 is most closely related to H. massardii and H. cevapii , 2 sequences that were absent in the analyses performed by Guitiérrez-Liberato et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The establishment of molecular techniques for the detection of blood parasites (Vilcins et al 2009 ) has revealed unexpectedly high levels of apicomplexan parasite diversity in amphibians and reptiles worldwide (O’Dwyer et al 2013 ; Tomé et al 2014 ; Harris et al 2015 ). For example, many new lineages and species of Hepatozoon of certain regions and host species have been identified using these techniques (e.g., Maia et al 2012 ; Rajabi et al 2017 ; Gutiérrez-Liberato et al 2021 ). In contrast, studies about amphibian and reptile haemosporidians are scarcer in the literature compared to those of haemogregarines (e.g., Fantham et al 1942 ; Martinele et al 2016 ; Matta et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%